"Fifty Shades of Agile": AN ANALYSIS OF DIFFERENT PERSPECTIVES OF AGILE SYSTEMS ENGINEERING. Issue 1 (13th September 2016) - Kemp, Duncan; Akroyd‐Wallis, Kirsty; Mactaggart, Ivan; Evans, Rhianne; Harrison, Kris; Woodcock, Hazel
Abstract: Although Agile is well‐defined, and relatively widely‐used within the software engineering field, applying Agile to Systems Engineering (SE) is still under debate. While some feel that Agile SE offers potential to improve customer satisfaction and reduce cost, risk and time to market, it is unclear how well Agile approaches apply to SE. This paper explores diverse rationales for applying Agile SE, various types of systems it can be applied to, and different Agile SE approaches, showing that there is no single definition of Agile. Views range from: a high tempo approach to systems delivery analogous to Agile software, radical tailoring of conventional SE against fixed requirements, using agile software techniques to develop SE documents and models, to using Agile as a sales mechanism with no real understanding of chance of success. These perspectives are analysed against the 12 Agile software principles, Snowdon's Cynefin Framework and Ring's Value Cycle, concluding with 14 observations about Agile SE approaches.